A global study on how the national business excellence (BE) custodians design BE frameworks and promote, facilitate, and award BE in their countries : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Engineering at Massey University, Manawatu Campus, New Zealand - Ghafoor, Saad (Massey University, 2021)
Business Excellence (BE) is a philosophy and a collection of BE Frameworks (BEFs) for organisations to follow to achieve excellence in strategies, business practices, and stakeholder-related performance results, to ultimately become the best they possibly can be. This research aimed to investigate the current state of and best practices in designing BEFs and deploying (promoting, facilitating, and awarding) BE on a national and/or regional level. The aim of this research was met through first conducting a systematic review of BE literature followed by collecting data directly from BECs. A mixed methodology and pragmatic philosophy were used in this research, thus collecting and analysing both quantitative and qualitative data. With regards to the participants of the research, 29 BECs from 26 countries undertook a 46-question survey. Of the survey participants, 13 BECs also undertook optional follow-up online structured interviews. It was found that while the BE literature comprises of 415 journal papers, no research covers how BECs support BE in their countries. There are 74 countries and four regions with BE Custodians (BECs) that promote BE within their countries, of which 57 actively hold BE Awards (BEA) with their last award held in 2018 or after. A key finding of this research is that BECs focus more on their BEA activities than their BE promotion and facilitation activities and report low levels of BE awareness and usage levels. A general framework for designing and reviewing a BEF is provided along with recommendations for BECs to improve their BE promotion, facilitation, and award activities. The findings of this research will help the national BECs to better understand their strengths and opportunities for improvement and to learn from other BECs’ practices. This will assist the BECs to better foster a culture of BE in their countries’ organisations that follow or aim to undertake a BE journey (of using a BE and adopting outstanding practices to achieve results) to ultimately benefit all of their stakeholders and lead to improved economic and societal benefits at a national level.
Keywords: Industrial efficiency; Evaluation; Success in business; Total quality management; 350715 Quality management